Genetics and genomics of African Rice (Oryza glaberrima Steud) domestication - Wambugu, P.W.; Ndjiondjop, M.N.; Henry, R. (Springer, 2021)
African rice (Oryza glaberrima Steud) is one of the two independently domesticated rice species, the other one being Asian rice (Oryza sativa L.). Despite major progress being made in understanding the evolutionary and domestication history of African rice, key outstanding issues remain controversial. There appears to be an underlying difficulty in identifying the domestication centre and number of times the crop has been domesticated. Advances in genomics have provided unprecedented opportunities for understanding the genetic architecture of domestication related traits. For most of the domestication traits, the underlying genes and mutations have been identified. Comparative analysis of domestication genes between Asian and African rice has revealed that the two species went through an independent but convergent evolution process. The genetic and developmental basis of some of the domestic traits are conserved not only between Asian and African rice but also with other domesticated crop species. Analysis of genome data and its interpretation is emerging as a major challenge facing studies of domestication in African rice as key studies continue giving contradictory findings and conclusions. Insights obtained on the domestication of this species are vital for guiding crop improvement efforts.